Design of Base Plates for Wide Flange Columns: A Concatenation of Methods - Thornton, William A. (Engineering Journal, 1990)
The Murray Stockwell (MS) method for design of base plates has the capability of producing very thin, and hence economical, small base plates for lightly loaded columns. The method has two problems, however, which make its incorporation into a general method for all base plates, i.e., large as well as small plates, and heavily as well as lightly loaded plates, difficult. First, the boundary between lightly and heavily loaded plates is not defined. Application of the MS method to a particular situation can lead to a base plate thicker than would be required by the AISC 8th Ed. Manual method, or can lead to a numerical failure of the method as indicated by mathematically imaginary solutions in terms of complex numbers. This problem has been demonstrated by Ahmed and Kreps. Second, the MS method assumes a peak bearing pressure of Fp over an H-shaped region adjacent to the column crosssection whereas the conventional assumption (i.e., AISC Manual 8th Ed. and AISC LRFD Manual 1st Ed.) is a uniform pressure fp over the entire contact area between the plate and the concrete. This problem led the author to propose a yield line method (referred to as Model 2 in Ref. 5) to replace the MS method for small base plates. Ref. 5 demonstrates that Model 2 coupled with the cantilever method for large base plates yields plate thicknesses equal to or less than the AISC 8th Ed. method. However, Model 2 yields thicker plates than the MS method when the plate is lightly loaded. In order to maintain the benefit of the MS method for lightly loaded plates, to define the boundary between lightly and heavily loaded plates, and to effect a merger of the two different pressure distributions and three methods into a single method, consider the following analysis.